Maracas Bay From The Mainland - (:unkn) unknown (Bon Genie Ltd., Trinidad, 2009)
After driving through the hills from Port of Spain you come to the entrance to Maracas Bay with the coconut tree lined beach and the hilly headland beyond. Postcard number B23.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Beaches--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maracas Bay